If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3d + 6)(4d + -11) = 0 Reorder the terms: (6 + 3d)(4d + -11) = 0 Reorder the terms: (6 + 3d)(-11 + 4d) = 0 Multiply (6 + 3d) * (-11 + 4d) (6(-11 + 4d) + 3d * (-11 + 4d)) = 0 ((-11 * 6 + 4d * 6) + 3d * (-11 + 4d)) = 0 ((-66 + 24d) + 3d * (-11 + 4d)) = 0 (-66 + 24d + (-11 * 3d + 4d * 3d)) = 0 (-66 + 24d + (-33d + 12d2)) = 0 Combine like terms: 24d + -33d = -9d (-66 + -9d + 12d2) = 0 Solving -66 + -9d + 12d2 = 0 Solving for variable 'd'. Factor out the Greatest Common Factor (GCF), '3'. 3(-22 + -3d + 4d2) = 0 Factor a trinomial. 3((-2 + -1d)(11 + -4d)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(-2 + -1d)' equal to zero and attempt to solve: Simplifying -2 + -1d = 0 Solving -2 + -1d = 0 Move all terms containing d to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1d = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1d = 0 + 2 -1d = 0 + 2 Combine like terms: 0 + 2 = 2 -1d = 2 Divide each side by '-1'. d = -2 Simplifying d = -2Subproblem 2
Set the factor '(11 + -4d)' equal to zero and attempt to solve: Simplifying 11 + -4d = 0 Solving 11 + -4d = 0 Move all terms containing d to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -4d = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -4d = 0 + -11 -4d = 0 + -11 Combine like terms: 0 + -11 = -11 -4d = -11 Divide each side by '-4'. d = 2.75 Simplifying d = 2.75Solution
d = {-2, 2.75}
| 10x+3x-4= | | 12x-3x+6x+5x= | | 2x(x+5)=870 | | 5y=4y^2-6 | | 2x^2-20x-44=0 | | 6c^2-11c+3=0 | | x^5-789=0 | | 2x+3x-3+10=4x+14 | | 6x+6=-112-10x | | 12x^4+12x^3-9x^2+16x-4=0 | | 27=0.428x | | 7x+3x-4x+11=7x+17-4x | | 6x^2=2x+2 | | 6(3x+3)=-198 | | -10=0.8y+6 | | -5x+4=-3x-2 | | 6x-3+2x=-67 | | 6x-3+2x=-64 | | 4(6x+2)=-112 | | -6x+1=5x+45 | | -23=3x+x+1 | | -7x-8=-1 | | 6(2x-1)=8x-2 | | 9x+5=4x+50 | | -x+9=-6+2x | | 0.85x+3y=0 | | -3x+4=-12+5x | | 2-x=-4x-10 | | -1+7x=5x-23 | | 6x-33=-x-5 | | 35000+250x=14 | | -2x+6=7x-21 |